ANALYSIS OF THE QUALITY OF THE INFINITE LEARNING TRAINING COURSE WEBSITE AT INFINITE LEARNING USING THE WEBQUAL 4.0 METHOD AND IMPORTANCE PERFORMANCE ANALYSIS (IPA) - Avicena, Ginanjar Ilmi Nur; Makky, Muhammad Al; Oktaviani, Ikke Dian (JIPI (Jurnal Ilmiah Penelitian dan Pembelajaran Informatika), 2025)
The training course sector in Indonesia has experienced rapid development in recent years. Many institutions offer various training courses to enhance skills and knowledge across different fields, from information technology to human resource management, with one such institution being Infinite Learning. The objective of this research is to assess the quality of the website and identify the factors that can improve its quality. Utilizing the Webqual 4.0 method as an evaluation indicator and Importance Performance Analysis to categorize the factors into quadrants based on the analysis of Importance Performance Analysis. Before data grouping, validity tests, reliability tests, and gap analysis between user expectations and perceptions need to be conducted. This step aims to strengthen the conclusions and recommendations produced after the research is completed. After conducting the research, the final results show that the Infinite Learning training course website has not met user expectations. This is evident from the gap analysis, which resulted in a score of -0.63, indicating that user expectations or importance are higher than the performance of the Infinite Learning training course website. The results of this research show that all performance values of each attribute are greater than the Importance values, indicating that users are satisfied with the services of the Infinite Learning training course website, with the highest value in the dimension of interaction quality at 0.93.